Visuality, Emotions and Minority Culture : Feeling Ethnic - Erni, John Nguyet (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book, stemming from an international conference, mainly explores the "private sphere" of minority cultures. To date, insufficient attention has been paid to ethnic minorities' sense of subjecthood, e.g. their construction and articulation of self-understanding formed through lived experiences, sensibilities, emotions, sentiments, empathy, and even tempers and moods. Social misunderstanding, not to mention stereotyping, mystification and discrimination, often stems from neglecting the surprising and enlivening texture of minorities' emotional world. Taking the important cue of the "affective turn" in cultural theory in recent years, the contributors address questions such as: what are the representations of affective/emotional energies and intensities surrounding the ethnic figures/strangers in visual culture (e.g. passivity, shame, anger, joy, empathy, charm, belonging, etc.)?; how do ethnic minorities respond to these visual narratives, and how can their self-representation through visual discourse reveal and transform their lived experiences?
Keywords: Social sciences.; Culture -- Study and teaching.; Ethnology.; Cultural studies.; Communication.; elektronické knihy; electronic books